Pseudomonas keratitis predominance in government hospitals in Johor, Malaysia - Balasegar, Vidhubala; Md Saleh, Rafidah; Than, Leslie Thian Lung; Jasni, Azmiza Syawani; Ibrahim, Rosni (Universiti Putra Malaysia Press, 2024)
Introduction: Keratitis is an eye-threatening condition, which requires immediate treatment, due to the rapid progression when the infection caused by Pseudomonas aeruginosa. This study aimed to describe the socio-demographic factors and risk factors related to Pseudomonas keratitis in selected six government hospitals in Johor, Malaysia. Methods: An 18 months cross-sectional study was conducted among bacterial keratitis patients from six government hospitals offering ophthalmology services in Johor, Malaysia. The cases were confirmed through a positive culture of Pseudomonas aeruginosa. All data on socio-demographic factors, risk factors, and symptoms were recorded using a data collection form and analysed using the Statistical Package for Social Sciences (SPSS) software version 26. Results: Fifty-five patients were diagnosed with Pseudomonas keratitis in this study. The majority of patients were males (65.5%) with a mean age of 41.22 years old. The majority of patients were of Malay ethnicity (60.0%). More than a quarter of cases are involved in office-oriented jobs (n=14, 25.5%). The major risk factors in this study were contact-lens usage (n=25, 45.5%), trauma (n=20, 36.4%), ophthalmic steroid usage (n=16, 29.1%), ocular surface disease (n=12, 21.8%) and previous eye surgery (n=4, 7.3%). This study found underlying medical illness (p=0.036) and ocular surface disease (p=0.051) are significantly associated with Pseudomonas keratitis. Conclusion: The present study is the first study in Malaysia focusing on Pseudomonas keratitis. This study provides additional information on the epidemiology data of keratitis in Malaysia. Future studies shall be extended to all government hospitals in Malaysia to obtain better insight on the disease burden of keratitis especially on Pseudomonas keratitis.